Boosted Meat Flavor by the Metabolomic Effects of Nile Tilapia Dietary Inclusion of Zophobas atratus Larval Meal - Yanfeng Li; Haozheng Li; Ge Zhang; Jiale Liu; Dawa Drolma; Bo Ye; Manjun Yang (Frontiers in Bioscience-Landmark)
Background: Zophobas atratus larval meal (ZLM) is a high-quality feed supplement with potential activities that can improve fish growth performance and promote meat quality. However, there have been limited recent studies investigating the metabolic effects of ZLM. Therefore, this study aims to uncover the metabolomic mechanism through which ZLM improves tilapia meat flavor using metabolomic strategies. Method: In this study, soybean meal in the basal diets was replaced with 15%, 30%, or 60% ZLM, where anti-nutrient factors were destroyed by high temperature treatment. After being fed these ZLM supplements for 30 days, dorsal muscles were collected from tilapia for meat sensory evaluation tests. Liver samples were also collected for metabolomic analysis using the gas chromatography-mass spectrometry (GC-MS) platform and combined with biochemical assays to verify metabolism-related enzyme activities and reveal crucial metabolic pathways and critical biomarkers associated with ZLM’s ability to improve meat flavor. Results: In tilapia livers, ZLM enhanced the activity of enzymes involved in energy metabolism including succinate dehydrogenase (SDH), pyruvate dehydrogenase (PDH), α-ketoglutarate dehydrogenase (α-KGDH), NADP-malate dehydrogenase (NAD-MDH) and mitochondrial isocitrate dehydrogenase (ICDHm). This resulted in increased levels of reduced nicotinamide adenine dinucleotide (NADH), acetyl CoA and ATP which led to accumulation of flavor fatty acids such as arachidonic acid, linoleic acid (9,12-Octadecadienoic acid), linolenic acid (9,12,15-Octadecatrienoic acid) and oleic acid (9-Octadecenoic acid). Additionally, there was an increase in flavor nucleotides like guanosine adenosine-5′-monophosphate and uridine-5′-monophosphate while off-flavor metabolites like inosine and hypoxanthine decreased. Furthermore, beneficial metabolomic responses led to a decrease in off-flavor metabolites such as 2-methylisoborneol trimethylamine and geosmin while increasing umami metabolites like 2-methyl-3-furanthiol and nonanal. Conclusions: This metabolomic study demonstrates that inclusion of ZLM diets enhances the flavor profile of tilapia dorsal muscle. The accumulation of flavor compounds, coupled with a reduction in earthy taste and off-flavor metabolites, contributes to an improved meat flavor and freshness. Additionally, there is an increase in the levels of flavor-related amino acids and nucleotides. These previously unidentified metabolic effects highlight the potential significance of ZLM as a dietary supplement for enhancing the biosynthesis of flavor metabolites in tilapia.